Arash Ramezanpour shahi - Ramezanpour shahi, Arash; Mamashli, Meysam; Ghorbani, Behnam (Journal of Poultry Sciences and Avian Diseases, 2025)
The aim of this study was to evaluate the impacts of different levels of Spirulina platensis supplementation on the mucosal morphology of the intestine of broiler chickens. Spirulina, a single-celled algae, has been recently categorized as a filamentous, gram-negative Cyanobacterium, which offers significant benefits in broiler nutrition by improving growth performance through its high protein content, enhancing immune function, boosting feed conversion efficiency, and supporting gut health. A total of 375 one-day-old male Arian broilers were included in a 6-week trial. The chicks were randomly assigned to five treatment groups, each with five replicates of 15 birds, received different concentrations of Spirulina in their drinking water: Group A (5 g/L), Group B (2.5 g/L), and Group C (1 g/L), while the control groups received either no additive or an antibiotic (Fosbac Biotic®). This study examined the effects of dietary Spirulina platensis supplementation on cecal, the height of intestinal villi, and the depth of crypts in Arian strain broiler chickens examined. The results indicated Spirulina increased villus height, reduced crypt depth, and improved the villus-to-crypt ratio in the duodenum jejunum and ileum, suggesting enhanced nutrient absorption. Moreover, Spirulina supplementation increased beneficial bacteria (lactobacilli) and reduced harmful bacteria (coliforms), improving overall gut health and reducing digestive problems. Further research is advised to explore the economic benefits of using Spirulina in the poultry industry.